(untitled) (Ibrahim Medical College Journal, 2010)
A 51 year old man presented with multiple painless skin nodules throughout his body for 3 weeks. He complained of cramping pain in his calf muscles and thighs for 3 months, occasional fever with chills for 2 months and lost about 10kgs in these 3 months. Initially he was diagnosed as a case of viral myositis. His CPK and LDH were raised, febrile antigens and widal test were negative, CA 19-9 was very high (5018 u/ml). Biopsy of skin nodules showed features of metastatic adenocarcinoma. Ibrahim Med. Coll. J. 2010; 4(1): 31-33 Key word: Cutaneous metastasis; adenocarcinoma DOI: 10.3329/imcj.v4i1.5933